ANALISIS PEMBERIAN MOTIVASI OLEH GURU PAK DALAM MENINGKATKAN HASIL BELAJAR AFEKTIF SISWA KELAS VIII SMP NEGERI 1 LINTONG NI HUTA KABUPATEN HUMBANG HASUNDUTAN TAHUN PEMBELAJARAN 2017/2018 - Sinaga, Desi Chrismawaty (Areopagus : Jurnal Pendidikan Dan Teologi Kristen, 2018)
This research intent to know big application percentage motivates to study by PAK teacher in increase afektifâ€™s studying result VIII class student SMP Country 1 Lintongnihuta learning year 2017/2018 by total population 142 person and sample is taken 60% totals 85 perseon. Instrument is research as questionnaire is closed as much item which is arranged own by researcher and was tested validity and reliability. Of data analysis result is gotten assesses implement as big as 82.02% lie on pretty good category. Base quiz t acquired Ýà¯”à¯£à¯ à¯¢à¯–à¯§à¯œà¯¡à¯š Ýà¯§à¯”à¯•à¯Ÿà¯˜ which is 10.93% 1.671 on ßª 0.05, hipotesiâ€™s mean Ð… gets to be accepted by its truth. Therefore Ha accepted and Ho is refused, which is Analisis is Application Motivates by PAK Teacher in Increase Afeltifâ€™s Studying Result VIII class Student SMP Country 1 Lintongnihuta Humbang Hasundutanâ€™s Regency Learning Year 2017/2018 75% of one are expected and accepted by its truth. Key word: Applicaton Motivaties, Afektifâ€™s Learned Result Student